Pilomatricoma: Forget me not - Lakshmi Narayan Garg; Sanjay Arora; Sunita Gupta; Sanjeev Gupta; Prem Singh (Indian Dermatology Online Journal, 2011)
Pilomatricoma is a benign skin neoplasia, which is not commonly encountered in general practice. The diagnosis is often made only after histopathology. The present case report is of a 30-year-old woman who presented with swelling in neck, which was diagnosed as pilomatricoma only after excision. The idea of reporting this case is that pilomatricoma is not rare in occurrence but rarely diagnosed because of lack of confirmation of excised swelling and it is imperative that it should be kept in the differential diagnoses of all superficial skin tumors by dermatologists and surgeons.